Not all KIT 557/558 codons mutations have the same prognostic influence on recurrence-free survival: breaking the exon 11 mutations in gastrointestinal stromal tumors (GISTs). (September 2021) - Incorvaia, Lorena; Badalamenti, Giuseppe; Fanale, Daniele; Vincenzi, Bruno; Luca, Ida De; Algeri, Laura; Barraco, Nadia; Brando, Chiara; Bonasera, Annalisa; Bono, Marco; Castiglia, Marta; Cancelliere, Daniela; et al.
Background: Although the gastrointestinal stromal tumor (GIST) genotype is not currently included in risk-stratification systems, a growing body of evidence shows that the pathogenic variant (PV) type and codon location hold a strong prognostic influence on recurrence-free survival (RFS). This information has particular relevance in the adjuvant setting, where an accurate prognostication could help to better identify high-risk tumors and guide clinical decision-making. Materials and Methods: Between January 2005 and December 2020, 96 patients with completely resected GISTs harboring a KIT proto-oncogene receptor tyrosine kinase ( KIT ) exon 11 PV were included in the study. We analyzed the type and codon location of the PV according to clinicopathological characteristics and clinical outcome; the metastatic sites in relapsed patients were also investigated. Results: Tumors harboring a KIT exon 11 deletion or deletion/insertion involving the 557 and/or 558 codons, showed a more aggressive clinical behavior compared with tumors carrying deletion/deletion/insertion in other codons, or tumors with duplication/insertion/single-nucleotide variant (SNV) (7-year RFS: 50% versus 73.1% versus 88.2%, respectively; p < 0.001). Notably, among 18 relapsed patients with 557 and/or 558 deletion or deletion/insertion, 14 patients (77.8%) harbored deletions simultaneously involving 557 and 558 codons, while only 4 patients (22.2%) harbored deletions involving only 1 of the 557/558 codons. Thus, when 557 or 558 deletions occurred separately, the tumor showed a prognostic behavior similar to the GIST carrying deletions outside the 557/558 position. Remarkably, patients with GISTs stratified as intermediate risk, but carrying the 557/558 deletion, showed a similar outcome to the high-risk patients with tumors harboring deletions in codons other than 557/558, or duplication/insertion/SNV. Conclusion: Our data support the inclusion of the PV type and codon location in routine risk prediction models, and suggest that intermediate-risk patients whose GISTs harbor 557/558 deletions may also need to be treated with adjuvant imatinib like the high-risk patients.